World Octopus Fisheries. Issue 3 (6th July 2021) - Sauer, Warwick H. H.; Gleadall, Ian G.; Downey-Breedt, Nicola; Doubleday, Zöe; Gillespie, Graham; Haimovici, Manuel; Ibáñez, Christian M.; Katugin, Oleg N.; Leporati, Stephen; Lipinski, Marek R.; Markaida, Unai; Ramos, Jorge E.; et al.
Abstract: Recent studies have shown that coastal and shelf cephalopod populations have increased globally over the last six decades. Although cephalopod landings are dominated by the squid fishery, which represents nearly 80% of the worldwide cephalopod catches, octopuses and cuttlefishes represent ∼10% each. Total reported global production of octopuses over the past three decades indicates a relatively steady increase in catch, almost doubling from 179, 042 t in 1980 to 355, 239 t in 2014. Octopus fisheries are likely to continue to grow in importance and magnitude as many finfish stocks are either fully or over-exploited. More than twenty described octopus species are harvested from some 90 countries worldwide. The current review describes the major octopus fisheries around the globe, providing an overview of species targeted, ecological and biological features of exploited stocks, catches and the key aspects of management.